PRODUCT QUALITY AND PRICE FAIRNESS ON PURCHASE DECISIONS THROUGH DISTRIBUTION CHANNELS - Astanto, M. Tony Andy; Abdullah, Thamrin; Karunia, Luki; Marwan, Jubery; Utama, Zahera Mega (KELOLA: Jurnal Ilmiah Manajemen, 2024)
The research was conducted with the aim of knowing the description of product quality, price fairness and distribution channels on purchasing decisions at PT Dynatech International. As well as knowing the role of distribution channels in mediating product quality and price fairness on purchasing decisions at PT Dynatech International. The study was studied using the post-positivism paradigm, with quantitative research methods. The population of the study was consumers of PT. Dynatech International totaling 250 people. The data used were primary data in the form of questionnaires measured using the Likert scale. The study used the Structural Equation Model-Partial Least Square approach with a measurement model using the Smart PLS version 3 program. The results of the study directly show that Product Quality and Price Fairness have an influence on Distribution Channels. Product Quality, Price Fairness, and Distribution Channels directly have an influence on Purchasing Decisions. While indirectly Distribution Channels mediate the influence of Product Quality and Price Fairness on Purchasing Decisions. From the research results, it can be concluded that Distribution Channels have the strongest influence on Purchasing Decisions. While Price Fairness has the weakest influence on Purchasing Decisions.